Feminist and Behavioural Economics - Austen, S.; Jefferson, Therese (Greenwood Publishing Group, 2015)
The first and only encyclopedia to focus on the economic and financial behaviors of consumers, investors, and organizations, including an exploration of how people make good—and bad—economic decisions. * Contains an informative ...